2010
DOI: 10.1227/neu.0b013e3181f918cf
|View full text |Cite
|
Sign up to set email alerts
|

Less Invasive Surgical Correction of Adult Degenerative Scoliosis. Part II: Complications and Clinical Outcome

Abstract: Less invasive image-guided correction of degenerative scoliosis in elderly patients with significant comorbidity yields a favorable complication profile. Significant improvements in spinal balance, pain, and functional scores mirrored expedited ambulation and early resumption of daily activities. Less invasive techniques appear suitable to reduce periprocedural morbidity, especially in elderly patients and individuals with significant medical risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…Cumulative radiation dose can exceed regulatory occupational limits[25],[26]. With current CT and 3-dimensional fluoroscopy-based navigation systems, the patient is exposed to significant amounts of radiation during image acquisition even if the surgeon is able to step away[18],[27]. This study confirmed that the use of the “L” shaped measuring device significantly reduced fluoroscopy time.…”
Section: Discussionsupporting
confidence: 71%
“…Cumulative radiation dose can exceed regulatory occupational limits[25],[26]. With current CT and 3-dimensional fluoroscopy-based navigation systems, the patient is exposed to significant amounts of radiation during image acquisition even if the surgeon is able to step away[18],[27]. This study confirmed that the use of the “L” shaped measuring device significantly reduced fluoroscopy time.…”
Section: Discussionsupporting
confidence: 71%
“…10,18,29,33,44,45,56 However, the utility of this technique in the treatment of spinal deformity, specifically with respect to adult degenerative scoliosis, has not been formally evaluated in greater detail. 2,3,10,11,18,31,34,46,47,56,60 With release of the lateral annuli, distraction across the disc space, and placement of a large interbody graft across the entire length of the endplates, the minimally invasive LLIF approach has become a powerful tool in the armamentarium in spinal deformity correction procedures. Indeed, when combined with PSIF, it has been reported to be effective in providing varying degrees of correction of degenerative lumbar scoliotic curves with less blood loss and less morbidity than traditional open procedures.…”
Section: Discussionmentioning
confidence: 99%
“…18,35,41,47,51,54 High ODI, high VAS scores, and low 12-Item Short Form Health Survey (SF-12) scores were associated with an improvement in symptoms. A baseline SF-12 score of 35 or less, for example, was 6 times more likely to improve compared with an initial score higher than 35.…”
Section: Clinical Outcomementioning
confidence: 99%